Design and Optimization of a Citrus Essential Oil Extraction System by Steam Distillation with Automated Control in Lima, Peru - Torres Taipe, Anderson Luigui (2024)
The production of essential oils is widely used in the world to combat various diseases. In addition, these oils are essential in the seasoning and flavoring of food and have applications in the field of cosmetology, helping to reduce environmental pollution by avoiding the use of chemical products. Peru is one of the fourteen most outstanding countries for its rich biodiversity in flora and fauna, and is also the sixth largest exporter of citrus fruits in the world. Therefore, a citrus essential oil extraction process is analyzed through the design of an industrial-scale essential oil distillation machine. This design includes the automation of the filling and emptying of the distiller to improve the results, as well as the implementation of a closed-loop control system for cooling. The objective is to facilitate operator control and monitoring of the cooling and water filling process through a control panel. After analyzing the distillation process, an average of 1% to 2% of essential oil and 50% of citrus peel hydrolate has been obtained, setting a new standard in the production of essential oils in the country.